Ways forward for resilience thinking: lessons from the field for those exploring social-ecological systems in agriculture and natural resource management - Katrina, Sinclair (Resilience Alliance, 2018)
Resilience thinking appears to offer a holistic approach that can be used by social researchers to interpret past and contemporary conditions and identify possible futures for social-ecological systems (SES). Resilience thinking is shaping contemporary environmental policy and its implementation in Australia, Europe, and North America. At the same time, social researchers have raised concerns about the limitations of resilience thinking, particularly in its handling of human agency, power relationships, social thresholds, and the social construction of SES definitions. We argue for a reflexive turn in resilience thinking as a way to address these concerns. We draw on lessons from three Australian case studies where a reflexive application of resilience thinking generated insights for research and practice. We propose six areas for reflexive inquiry: (1) focal scale and level, (2) SES definition, (3) narratives of change, (4) processes of knowledge production, (5) social transition trajectories, and ( 6) social thresholds. In so doing, the assumptions of resilience thinking are politicized and problematized, which improves its theoretical analytical utility, and in practice generates new insights into social processes. Reflexivity offers opportunity for greater cross-disciplinary dialogue between resilience thinking and the social sciences, while allowing methodologies with differing ontologies and epistemologies to be applied in a complementary manner.